2001
DOI: 10.1104/pp.126.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of a Lytic Central Vacuole and of Neutral Peripheral Vacuoles Can Be Visualized by Green Fluorescent Proteins Targeted to Either Type of Vacuoles

Abstract: Protein trafficking to two different types of vacuoles was investigated in tobacco (Nicotiana tabacum cv SR1) mesophyll protoplasts using two different vacuolar green fluorescent proteins (GFPs). One GFP is targeted to a pH-neutral vacuole by the C-terminal vacuolar sorting determinant of tobacco chitinase A, whereas the other GFP is targeted to an acidic lytic vacuole by the N-terminal propeptide of barley aleurain, which contains a sequence-specific vacuolar sorting determinant. The trafficking and final acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
139
0
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(150 citation statements)
references
References 33 publications
5
139
0
6
Order By: Relevance
“…Anthocyanins Share a Golgi-Independent, Vesicular Trafficking Pathway with Proteins Targeted to the PSV The plant secretory system involves multiple pathways for the transport of proteins to the vacuole (Carter et al, 2004), and GFP fusion markers (Chalfie et al, 1994) permit distinguishing between them (Neuhaus, 2000;Di Sansebastiano et al, 2001). To establish whether the ER or ER bodies are a possible initial site of anthocyanin accumulation, as previously suggested for maize (Grotewold et al, 1998) and recently described for flavonols in Brassica and Arabidopsis tapetum cells (Hsieh and Huang, 2007), Arabidopsis seedlings transformed with GFP-HDEL (Haseloff et al, 1997), where HDEL corresponds to an ER-retention signal sequence, were grown under anthocyanin inductive conditions, with (1N) or without (2N) naringenin (Fig.…”
Section: Novel Fluorescent Properties Of Arabidopsis Anthocyaninsmentioning
confidence: 99%
See 3 more Smart Citations
“…Anthocyanins Share a Golgi-Independent, Vesicular Trafficking Pathway with Proteins Targeted to the PSV The plant secretory system involves multiple pathways for the transport of proteins to the vacuole (Carter et al, 2004), and GFP fusion markers (Chalfie et al, 1994) permit distinguishing between them (Neuhaus, 2000;Di Sansebastiano et al, 2001). To establish whether the ER or ER bodies are a possible initial site of anthocyanin accumulation, as previously suggested for maize (Grotewold et al, 1998) and recently described for flavonols in Brassica and Arabidopsis tapetum cells (Hsieh and Huang, 2007), Arabidopsis seedlings transformed with GFP-HDEL (Haseloff et al, 1997), where HDEL corresponds to an ER-retention signal sequence, were grown under anthocyanin inductive conditions, with (1N) or without (2N) naringenin (Fig.…”
Section: Novel Fluorescent Properties Of Arabidopsis Anthocyaninsmentioning
confidence: 99%
“…4, E-H) of transgenic Arabidopsis lines expressing vacuolar-sorting signals fused to GFP. The GFP-Chi marker, corresponding to a fusion of the GFP to the C-terminal vacuolar-sorting determinant from the barley (Hordeum vulgare) chitinase A protein, is targeted to pH-neutral PSVs directly from the ER in a Golgiindependent manner (Di Sansebastiano et al, 1998Sansebastiano et al, , 2001Fluckiger et al, 2003). Arabidopsis seedlings transgenic for 35STGFP-Chi grown in anthocyanin inductive conditions for 3 d show green fluorescence provided by GFP-Chi in discrete structures that could correspond to the ER and to small peripheral vacuoles (Fig.…”
Section: Novel Fluorescent Properties Of Arabidopsis Anthocyaninsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, we had to show that this petunia aleurain sequence was sufficient for vacuolar sorting in plants by using GFP as a reporter. In our laboratory, we had already used the whole propeptide (119 amino acids) from barley aleurain fused to GFP and found that the reporter accumulated in an acidic vacuole (Di Sansebastiano et al, 2001). This necessitated the use of a more stable and brighter variant of GFP5, called GFP6, which differs from GFP5 by the mutations F64L and S65T described previously (Cormack et al, 1996).…”
mentioning
confidence: 99%